Analysis of Illocutionary Act in A Quite Place Movie - Fitra Handayani; Ela Martisa (English Literature Study Program, Faculty of Humanities, Universitas Halu Oleo, 2023)
This research aims to describe the use of illocutionary acts in the film A Quite Place. This study used a descriptive qualitative method. This research uses Searle's theory to find the verbal and nonverbal utterances of all the characters included in the illocutionary act theory. Data collection is carried out by downloading, reading, watching, and classifying. Based on the theories provided, the data is analyzed one by one to determine the context and type of illocutionary act used. The results of the research show that there are four types of illocutionary acts used by all the characters in the film A Quiet Place 2018. The instructions present the dominant frequencies of the five types of illocutionary acts. There are six that contain directive actions. The assertive one has four data. Expressive has four data, the lowest frequency of illocutionary acts is commissive, there are two data. This type of declaration was not found in this study. The data most often found in this film is directive with six data and the least is commissive with two data. Based on the explanation above, it can be concluded that the problems that occurred in this research have been answered so that the research objective has been found and explained clearly, namely how illocutionary acts are used in the film A Quite Place using Searle's theory.